Impact of hospitalization on modification of drug regimens: Results of the criteria to assess appropriate medication use among elderly complex patients study. Issue 5 (28th May 2015) - Sganga, Federica; Landi, Francesco; Vetrano, Davide L; Corsonello, Andrea; Lattanzio, Fabrizia; Bernabei, Roberto; Onder, Graziano
Abstract : Aim: To assess the impact of hospitalization on modification of drug burden among elderly patients. Methods: The present prospective cohort study was carried out in acute care hospitals in Italy. The difference in the number of drugs used before hospital admission and those prescribed at discharge was calculated. The prevalence of (i) any increase (1 or more drugs); and (ii) an increase >50% in the number of drugs from admission to discharge was calculated, and the factors associated with these conditions were identified. Results: The mean age of 1082 participants was 81.2 ± 7.3 years and 606 were women (56.0%), an increase in the number of drugs (1 or more drugs) between admission and discharge was observed in 672 participants (62.1% of study sample) and an "increase >50%" was observed in 372 participants (34.3%). "Any increase" was inversely associated with age and the number of drugs used before hospitalization, and it was positively associated with length of stay and diagnoses, including chronic obstructive pulmonary disease, ischemic heart disease and diabetes. "Increase >50%" was inversely associated with female sex, the number of drugs before hospitalization, involuntary loss of weight and intact cognitive status, and was positively associated with length of stay, chronic obstructive pulmonary disease, heart failure and diabetes. Conclusions: Not only disease, but also demographic factors (age and gender) and geriatric syndromes (weight loss and cognitive status) might influence pharmacological burden. These data might be useful in order to target interventions aimed at improving drug use and reducing iatrogenic illness.Geriatr Gerontol Int 2016; 16: 593–599.